If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 238 = 7(7b + -1) Reorder the terms: 238 = 7(-1 + 7b) 238 = (-1 * 7 + 7b * 7) 238 = (-7 + 49b) Solving 238 = -7 + 49b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-49b' to each side of the equation. 238 + -49b = -7 + 49b + -49b Combine like terms: 49b + -49b = 0 238 + -49b = -7 + 0 238 + -49b = -7 Add '-238' to each side of the equation. 238 + -238 + -49b = -7 + -238 Combine like terms: 238 + -238 = 0 0 + -49b = -7 + -238 -49b = -7 + -238 Combine like terms: -7 + -238 = -245 -49b = -245 Divide each side by '-49'. b = 5 Simplifying b = 5
| -138=6(4n-3) | | n+8=n+2 | | 14+4n=8n-3(n-6) | | 5(5+2x)=105 | | 3x-y=37 | | 3ln(x-1)=15 | | 0.10x+0.10y=100 | | 1/6(x+4)=3x-4(2-x)-5 | | -114=6(-4+2a)+6a | | -9x-y=-59 | | 58-7x=11x+24 | | 2/5(2x+11)=3(4-3x)+12 | | 2/5x^2+1/5x-2=0 | | -6(1-6r)=138 | | 2/5(2x+11)=3(4x-3x)+12 | | -152=4(4k-6) | | -5n+18+3n=-6 | | n=2-3 | | -107=r+3(7r+1) | | 24x+19x= | | 8(h+3)=7(h-3) | | 25x^5y^3/50x^2y^7 | | 15m+23=-7m+18 | | -9+6v=v-5+6v | | 2X/4+3X/9 | | 2X/4+3X/9+4X/16+5X/25 | | 5a-6b-2a+3b= | | -q-13=2q+5 | | -1+3p=-1p-5p | | 8=4z-3z^2+15 | | x-12=48 | | -5x-2=4-4x |